Disaster cinema in historical perspective : mediations of the sublime - Mathias, Nikita (Amsterdam University Press, 2020)
'Disaster Cinema in Historical Perspective: Mediations of the Sublime is a genuine and original contribution to the fields of art history and cinema studies as well as to discussions on the concept of the sublime in the field of aesthetics. It is well-organized, well-informed, and lucidly written and draws on an impressive body of empirical and theoretical materials. As importantly, it is critical and nuanced in its claims and assertions, leaving ample room for discussion and counter-argument.' (Ina Blom, University of Chicago, University of Oslo).